Advancement of multidisciplinary education and research in translational sciences: MERITS program development at Duke University. Issue 1 (6th July 2018) - Freel, Stephanie A.; Fish, Laura J.; Mirman, Benjamin; Sudan, Ranjan; Devi, Gayathri R.
Abstract : Introduction: The Duke Multidisciplinary Education and Research in Translational Sciences Program provides educational resources for faculty and trainees in translational research. Methods: To aid in program development, we assessed perceptions of translational science through focus groups targeting different career stages. Results: In total, 3 essential themes emerged: collaboration, movement toward application, and public health impact. Facilitators and barriers varied among groups. Conclusion: Training programs must provide specific strategies for collaboration and selectively accelerating discoveries to therapies.